Separate groups of dopamine neurons innervate caudate head and tail encoding flexible and stable value memories - Kim, Hyoung F.; Ghazizadeh, Ali; Hikosaka, Okihide (Frontiers in Neuroanatomy, 2014)
Dopamine (DA) neurons are thought to be critical for reward value-based learning by modifying synaptic transmissions in the striatum. Yet, different regions of the striatum seem to guide different kinds of learning. Do DA neurons contribute to the regional differences of the striatum in learning? As a first step to answer this question, we examined whether the head and tail of the caudate nucleus of the monkey (Macaca mulatta) receive inputs from the same or different DA neurons. We chose these caudate regions because we previously showed that caudate head neurons learn values of visual objects quickly and flexibly, whereas caudate tail neurons learn object values slowly but retain them stably. Here we confirmed the functional difference by recording single neuronal activity while the monkey performed the flexible and stable value tasks, and then injected retrograde tracers in the functional domains of caudate head and tail. The projecting dopaminergic neurons were identified using tyrosine hydroxylase immunohistochemistry. We found that two groups of DA neurons in the substantia nigra pars compacta project largely separately to the caudate head and tail. These groups of DA neurons were mostly separated topographically: head-projecting neurons were located in the rostral-ventral-medial region, while tail-projecting neurons were located in the caudal-dorsal-lateral regions of the substantia nigra. Furthermore, they showed different morphological features: tail-projecting neurons were larger and less circular than head-projecting neurons. Our data raise the possibility that different groups of DA neurons selectively guide learning of flexible (short-term) and stable (long-term) memories of object values.